33. THE RELATIONSHIP BETWEEN ROLE OVERLOAD, MARITAL SATISFACTION, AND THE LEVEL OF DEPRESSIVE SYMPTOMS IN FIRST-TIME MOTHERS (Vietnam Journal of Community Medicine, 2024)
Ojective: This research aims to investigate the relationship between role overload, marital satisfaction, and the level of depressive symptoms, with role overload being considered as a moderating factor in the relationship between marital satisfaction and the level of depressive symptoms, especially in first-time mothers.Methods: The study was conducted using both direct and online surveys with participants being 148 married women who had children aged 6 to 24 months and primarily residing in Ho Chi Minh City and some provinces in Vietnam.Results: The results of the analysis revealed two inverse relationships: The role overload (r = -0.440, p < 0.001) and the level of depressive symptoms (r = -0.395, p < 0.001) tend to increase as marital satisfaction decreases. Additionally, the study identified a positive correlation between role overload and the level of depressive symptoms (r = 0.546, p < 0.001). However, the research did not have a demonstrate the role overload factor the moderating effect (p > 0.005).Conclusion: The study suggests examining cultural and living context factors for women transitioning into motherhood in the typical collective culture of Vietnam. This might include factors related to perspectives on the mother's role, and support from extended family members.
Keywords: First-time mothers, role overload, marital satisfaction, depressive symptoms